Taking Terrain Literally: Grounding Local Adaptation to Corporate Social Responsibility in the Extractive Industries - Dougherty, Michael L. (Journal of business ethics, 2014)
Since the early 1990s, the extractive industries have increasingly valued corporate social responsibility (CSR) in the communities where they operate. More recently, these industries have begun to recognize the importance of adapting CSR efforts to unique local contexts rather than applying a one-size-fits-all model. However, firms understand local context to mean culture and treat the physical properties of the host region—topography, geology, hydrology, and climate—as the exclusive purview of mineral geologists and engineers. In this article, we examine the organization of CSR at two industrial-scale gold mines in Guatemala, owned by the same firm, which yielded starkly distinct levels of support among host community residents. We develop the idea of social terrain to convey the way in which the biophysical environment informs local social relations and imbues phenomena with particular social meanings. We argue that firms must account for social terrain in organizing for CSR. The literature struggles to provide guidelines for identifying and understanding stakeholders. Social terrain, we argue, can begin to bridge this gap between theory and practice.